2005
DOI: 10.1073/pnas.0500585102
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanism in anterior prefrontal cortex for inhibition of prolonged set interference

Abstract: Once one cognitive set dominates our behavior, it continues to influence subsequent behavior for a while even after a task to be performed is changed to another. Despite abundant knowledge of the inhibitory mechanisms that are recruited at the first trial after the change (the first inhibition trial), little is known about the inhibition of prolonged proactive interference from a previous set that lingers for several trials after the first inhibition trial. The present functional MRI study explored the neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 48 publications
1
49
2
Order By: Relevance
“…On the other hand, the two regressions (dmFC vs SSRT and rACC vs SSRT) were not significantly different in the current work, indicating that the suggested functional differentiation between the two brain regions is merely descriptive and needs to be confirmed in a larger cohort of subjects. Further studies are also warranted to examine whether rACC activity during stop signal inhibition can be generalized beyond the current behavioral task and whether rACC is similarly compromised in PCD during other executive control functions such as those that can be decomposed in the Wisconsin Card Sorting Task (Konishi et al, 2005;Lie et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the two regressions (dmFC vs SSRT and rACC vs SSRT) were not significantly different in the current work, indicating that the suggested functional differentiation between the two brain regions is merely descriptive and needs to be confirmed in a larger cohort of subjects. Further studies are also warranted to examine whether rACC activity during stop signal inhibition can be generalized beyond the current behavioral task and whether rACC is similarly compromised in PCD during other executive control functions such as those that can be decomposed in the Wisconsin Card Sorting Task (Konishi et al, 2005;Lie et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to the biasing hypothesis, the prefrontal cortex is the brain region that controls the activated LTM. Evidence for biasing comes from task-switching studies (Konishi et al, 2003(Konishi et al, , 2005Mayr, Diedrichsen, Ivry, & Keele, 2005) as well as from tasks requiring controlled memory retrieval (Sakai & Passingham, 2004; for reviews, see Bunge, 2004;Miller & Cohen, 2001).…”
Section: Implications To Prefrontal Functionsmentioning
confidence: 99%
“…In contrast to the rather phasic involvement of this area in reconfiguring task sets, the frontopolar cortex may exert a tonic influence over the task performance by maintaining task sets. In fact, it has been shown that the FPC is involved in sustained cognitive control during task switching (Braver et al, 2003) or in resolution of prolonged proactive interference from a previous cognitive set in the Wisconsin Card Sorting Test (Konishi et al, 2005).…”
Section: Set Activity In Fpc Predicts Subsequent Task Performancementioning
confidence: 99%